2016
DOI: 10.1002/ls.1363
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the design of textured surfaces for reducing lubricated friction coefficient

Abstract: Under operating conditions which are unfavourable for lubrication, such as high load and low velocity, the use of textured surfaces significantly promotes the formation of a thick lubricant film and an improvement of the friction coefficient. This paper relates to the manufacture of textures using a photolithography and chemical etching process. Different surface geometries, texturing densities and depths were designed to analyse the influence of these parameters. The friction coefficient was measured in a bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
1
13
0
9
Order By: Relevance
“…The microgroove depth is an important factor that affects the lubrication performance of the journal bearing and the thrust bearing. 1128 As shown in Figure 11(a) and (b), the load capacity reaches a maximum and the friction coefficient reaches a minimum at the groove depth of 2.0 μm and 2.5 μm for the eccentricity ratio of 0.2 and 0.4, respectively. Figure 11(a) and (b) also reveals that the load capacity continuously decreases with the increase in microgroove depth when the coupled effect is absent.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The microgroove depth is an important factor that affects the lubrication performance of the journal bearing and the thrust bearing. 1128 As shown in Figure 11(a) and (b), the load capacity reaches a maximum and the friction coefficient reaches a minimum at the groove depth of 2.0 μm and 2.5 μm for the eccentricity ratio of 0.2 and 0.4, respectively. Figure 11(a) and (b) also reveals that the load capacity continuously decreases with the increase in microgroove depth when the coupled effect is absent.…”
Section: Resultsmentioning
confidence: 89%
“…It has been demonstrated by numerical simulations and experiments that the textured/microgroove surface can facilitate in improving the lubrication performances for the conformal contact case. 1124 In addition, the bottom shape of the microgroove plays a crucial role in affecting the hydrodynamic performance. 25–27 Recently, studies have been performed to further understand the influence mechanism of the microgroove with different bottom shapes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otero et al [112] attempted to optimize surface micro-textures fabricated by photolithography and chemical etching processes in order to reduce the COF of EHL contacts by means of an ANN. The data was obtained from tests on a mini-traction machine (steel ball-on-micro-textured copper disk) at various loads, total speeds and slip conditions.…”
Section: Surface Texturingmentioning
confidence: 99%
“…Recent publications [1,[4][5][6][7][8][9][10][11][12][13] have shown that the pressure-generating effect of textured surfaces that operate in full film lubrication conditions may be the result of three different mechanisms: micro-cavitation [5][6][7][8]12,13] that happens when the pressure in a fluid suddenly drops due to an enlargement of the flow section, convective inertia [1,9] that consists of the inertial force due to the convective acceleration in a flow, and piezo viscosity [10,11], a pressure dependence of viscosity. However, from all these mechanisms that happen in textured surfaces, it seems that micro-cavitation can make a decisive contribution in order to understand the load-carrying capacity effect.…”
Section: Modelling Textured Surfacesmentioning
confidence: 99%